Parent–Child Estrangement: Conditions for Disclosure and Perceived Social Network Member Reactions. Issue 5 (December 2016) - Scharp, Kristina M.
Abstract : Disclosing a family disruption like estrangement might be an important first step in garnering supportive communication, yet disclosure also might come with costs. Grounded in the disclosure literatures, this study illuminates the conditions under which adult children disclose estrangement from parents to their social networks and the perceived reactions of social network members to such disclosures. Findings from a thematic analysis of 52 narrative interviews reveal that adult children go to great lengths to keep their estrangement private, but disclose (a) when others witnessed conflict, (b) when asked, (c) when disclosure was indirect, and (d) when (they perceived) it would benefit others. Reactions to disclosure were rarely ambivalent, and adult children primarily felt unsupported by their network. Practical applications are discussed.